2006
DOI: 10.1300/j013v44n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Low-Income Rural Women: Qualitative Insights About Physical Activity and Eating Patterns

Abstract: Body weight is inversely related to socioeconomic status (SES) in women in the United States (U.S.). Reasons for the social differential in weight are poorly understood. This investigation sought to understand overweight and obesity from the perspective of low-income mothers living in rural New York State, focusing in particular on challenges to maintaining a healthy weight that may be unique to rural poverty. In-depth interviews with 28 women, who were interviewed 3 times over a 3-year period, were audiotaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 32 publications
4
88
0
Order By: Relevance
“…A mixed-methods study by Bove and Olson (2006) among rural, low-income women revealed that obese informants were twice as likely to cite transportation difficulties compared to normal weight informants. Residing outside of population centres, with fewer opportunities to be active, limited women to sedentary activities at home.…”
Section: Environmental and Structural Barriers And Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed-methods study by Bove and Olson (2006) among rural, low-income women revealed that obese informants were twice as likely to cite transportation difficulties compared to normal weight informants. Residing outside of population centres, with fewer opportunities to be active, limited women to sedentary activities at home.…”
Section: Environmental and Structural Barriers And Facilitatorsmentioning
confidence: 99%
“…Residing outside of population centres, with fewer opportunities to be active, limited women to sedentary activities at home. In response to feelings of isolation and boredom, a consequence of being unable to leave home, respondents cited engaging in 'emotional eating' as a method of coping (Bove and Olson 2006). In addition to living in neighbourhoods with decreased walkability, obese women may be particularly discouraged from outside walking due to increased instability on slippery and uneven surfaces, especially in northern climates .…”
Section: Environmental and Structural Barriers And Facilitatorsmentioning
confidence: 99%
“…For example, Olson et al (2007) reported that women who had experienced food deprivation during their childhood were more likely to use food to meet their emotional needs, developed tendencies to overeat when they experienced negative emotions, were super-motivated to actively avoid food insecurity, and showed tremendous excitement toward food after periods of deprivation. Several studies have also documented that food insecurity and/or deprivation in childhood and adulthood resulted in mothers' disordered eating patterns such as food binges (Bove & Olson, 2006;Olson & Bove, 2005;Olson et al, 2007;Mammen, Bauer, & Richards, 2009). These patterns may be one factor contributing to the prevalence of overweightness and obesity among the low-income population.…”
Section: Findings Family Food Practice and Managementmentioning
confidence: 99%
“…Women residing in rural communities, especially those areas characterized by isolation and poverty, reported engaging in disordered eating and low levels of physical activity, which contributed to obesity risks (Bove & Olson, 2006).…”
Section: Maternal Health Outcomesmentioning
confidence: 99%
“…Even in rural areas with road access, travelling to larger, cheaper supermarkets may be hindered by transportation barriers such as travel distance, lack of a vehicle, and cost of gasoline, vehicle repair, and vehicle registration (Bove & Olson, 2006;Mercille et al, 2012).…”
Section: Setting and Populationmentioning
confidence: 99%